IDENTIFIKASI BAHAYA DAN RISIKO PADA AKTIVITAS PENGUPASAN PERMUKAAN TANAH DAN PENGANGKUTAN TOP SOIL DAN OVERBURDEN DI PT ALAM JAYA PRATAMA KUTAI KARTANEGARA - Hardiyono Hardiyono; Patunru Pongky; Komeyni Rusba; Impol Siboro; Adrian Pranajaya (Jurnal Ilmiah Hospitality, 2022)
Occupational Health and Safety (OHS) is in the interest of workers, employers and governments around the world. Coal mining is a long-term activity, involving high technology and capital intensive. Identification of occupational hazards and risks is an early stage that must be considered by the company. The purpose of this study is to identify hazards and risks as well as carry out risk assessment and risk control in stripping activities and transportation of top soil and overburden (OB) at PT. Alam Jaya Pratama Kutai Kartanegara. Data collection and regarding hazard identification and risk assessment are analyzed with IBPR then evaluated and determined for risk control efforts so that they can work safely. This research is a qualitative research, namely descriptive research. In the study there were 7 sources. The final result of the identification of hazards and risks are 27 identified hazard activities, and for the percentage before additional controls are carried out. Stripping activity and transportation of top soil, high 23%, medium 23% and low 54%. And the activity of stripping the soil surface and transporting overburden, high 21%, medium 21% and low 58%. After additional control was carried out, the percentage of risk experienced a good change with percentages, high 0%, medium 0% and low 100% in stripping activities and transporting top soil and overburden (OB). It is known that risk assessment and control are included in the effective category.